Female leadership in Ethiopian schools ten years ago - Tariku, Rahel (2022)
Living in Finland for the past eleven years has helped me to see the perspective of women’s leadership compared to my experience in Ethiopia. Finland is a small nation and is able to concord female leadership and believe in female leadership. Finnish women are very strong to rework on their lives and keep repositioning themselves in society until they have achieved their goals. I believe that with passion and focused minds Ethiopian women can also. Generally, in Ethiopia female leadership is a recent phenomenon. Despite that, women have played significant roles in contributing for education, politics, diplomacy, and power, since Ethiopia was considered as a nation three thousand years ago. Ethiopian women’s impact has been deterred by political and religious male leaders mainly because of the lack of education and of the fear among male leaders In addition, the very few educational opportunities for women have left Ethiopia with a high number of illiterate women. Furthermore, the highly educated women’s silence, the smaller number of women as educational leaders, specifically female school principals interest me to find out why there are so few female leaders in educational organisations in Ethiopia? This thesis is beyond female school leadership; it is a study of the past female leadership experience and the present training of female leaders in school leadership. The data collected ten years ago in Addis Ababa, Ethiopia but, most recent research work are sahwing the relevance of my data to present situation. I studied the current situation of female school leadership progress from grassroot level to see the dif erence in between 2011 and now 2023.I considered it necessary to study girls’ and boys’ equity and equality in Ethiopia as a possible cause for the small number of female school leaders in Ethiopia. Based on my findings, the enrollment of girls to primary, secondary, and tertiary education, and the small number of women in higher education can be seen as reasons for why female leadership is very limited in educational organizations in Ethiopia. Women have contributed equally to men in Ethiopia and can contribute to the progress of the nation. Women have equal capacity as men in dif erent fields.